KONTRIBUSI KEMATANGAN SOSIAL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN ANAK GANGGUAN INTELEKTUAL RINGAN DI DKI JAKARTA - Nirsantono Hasnul (Perspektif Ilmu Pendidikan, 2009)
The purpose of this correlation research was to know the contribution of social maturity to the reading comprehension competence of mentally retarded students of the fifth grades students at special school The research population covered the mentally retarded students at special schools in the east, west and south regions of Jakarta, selecting 30 students for the samples.applying stratified sampling technique. The hypothes was tested by product moment person correlation. The finding of the research showed socisl maturity contributed 87% to reading comprehension competence of the mentally retarded students in the fifth grade at special school. Based on the finding, the research provided a set of recommendations.